Upcoming legal challenges for cross-border e-health services in the EU - Janeckaitė, Rūta (Vilnius University Open Series, 2020)
The paper briefly describes the current EU legal framework in the healthcare field and assess to which extent it could apply to the provision of cross border eHealth services. In particular, it analyses the provision of such services from the free movement angle, i.e. whether EU law guarantees to health professionals access to and exercise of activiti es in the 3rd type of situations, as well as whether the insured persons have the right to reimbursement of costs of such healthcare from their social security system.
Keywords: Healthcare services provided via ICT; Telemedicine; The right to reimbursement of costs of crossborder telemedicine; Telemedicine services provided via collaborative economy platforms